Asian leadership : charisma and vision and thier impact on follower outcomes. - Lim, Lee Ping. (2008)
This study seeks to investigate the main effects of the two important leadership traits, charisma and vision, on follower-level outcomes of satisfaction, commitment and performance. The research was carried by collecting data from maunfacturing and service companies in Singapore.